Alcohol use in the year following approach bias modification during inpatient withdrawal: secondary outcomes from a double‐blind, multi‐site randomized controlled trial. (13th July 2022) - Manning, Victoria; Garfield, Joshua B. B.; Reynolds, John; Staiger, Petra K.; Piercy, Hugh; Bonomo, Yvonne; Lloyd‐Jones, Martyn; Jacka, David; Wiers, Reinout W.; Verdejo‐Garcia, Antonio; Lubman, Dan I.
Abstract: Background and aims: Approach bias modification (ApBM) targeting alcohol approach bias has been previously shown to reduce likelihood of relapse during the first 2 weeks following inpatient withdrawal treatment (IWT). We tested whether ApBM's effects endure for a longer period by analysing alcohol use outcomes 3, 6 and 12 months post‐discharge. Design: A double‐blind, sham‐controlled randomized controlled trial. Setting: Four IWT units in Melbourne, Australia. Participants: Three hundred alcohol IWT patients (173 men, 126 women, 1 non‐binary; mean age 43.5 years) were recruited between 4 June 2017 and 14 July 2019. Follow‐up data collection was completed on 22 September 2020. Intervention and control training: Four ApBM sessions were delivered during IWT. ApBM trained participants ( n = 147) to avoid alcohol and approach non‐alcohol beverage cues. Controls ( n = 153) responded to the same stimuli, but without approach/avoidance training. Measurements: Date of first lapse was recorded for non‐abstinent participants to determine time to first lapse. Time‐line follow‐back interviews assessed past‐month alcohol consumption at each follow‐up, with participants reporting no alcohol consumption classified as abstinent. In analyses of past‐month abstinence, non‐abstinence was assumed in participants lost to follow‐up. Number of past‐month drinking days, standard drinks and heavy drinking days (five or more standard drinks for women or non‐binary; six or more standard drinks for men) were calculated for non‐abstinent participants at each follow‐up. Findings: ApBM significantly delayed time to first lapse [ApBM median: 53 days, 95% confidence interval (CI) = 21–61; controls = 12 days, 95% CI = 9–21, P = 0.045]. Past‐month abstinence rates at 3‐, 6‐ and 12‐month follow‐ups were 33/153 (21.6%), 30/153 (19.6%), and 24/153 (15.7%) in controls; and 51/147 (34.7%), 30/147 (20.4%) and 29/147 (19.7%) in the ApBM group, respectively. Past‐month abstinence was significantly more likely in ApBM participants than controls at the 3‐month follow‐up [odds ratio (OR) = 1.93, 95% CI = 1.16–3.23, P = 0.012], but not at 6‐ or 12‐month follow‐ups (6‐month OR = 1.05, 95% CI = 0.60–1.95, P = 0.862; 12‐month OR = 1.32, 95% CI = 0.73–2.40, P = 0.360). No significant group differences were found for indices of alcohol consumption in non‐abstinent participants. Conclusions: Approach bias modification for alcohol delivered during inpatient withdrawal treatment helps to prevent relapse, increasing rates of abstinence from alcohol for at least 3 months post‐discharge.